2003
DOI: 10.1194/jlr.m200469-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ileal bile acid transport and reduced atherosclerosis in apoE−/− mice by SC-435

Abstract: These results suggest that specific inhibition of ASBT is a novel therapeutic approach for treatment of hypercholesterolemia resulting in a decreased risk for atherosclerosis. -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…This point is nicely illustrated in a study comparing the development of hypercholesterolemia and atherosclerosis in apoE-null mice lacking either the ASBT or OST ␣ ( 100 ). Similar to the effects of bile acid sequestrants ( 101 ) or ASBT inhibitors ( 102,103 ), levels of plasma and hepatic cholesterol and markers of atherosclerosis development were reduced in apoE-null mice lacking the ASBT. However, these markers were not reduced in apoE-null mice lacking OST ␣ .…”
Section: Enterocyte Metabolism Of Bile Acidsmentioning
confidence: 57%
“…This point is nicely illustrated in a study comparing the development of hypercholesterolemia and atherosclerosis in apoE-null mice lacking either the ASBT or OST ␣ ( 100 ). Similar to the effects of bile acid sequestrants ( 101 ) or ASBT inhibitors ( 102,103 ), levels of plasma and hepatic cholesterol and markers of atherosclerosis development were reduced in apoE-null mice lacking the ASBT. However, these markers were not reduced in apoE-null mice lacking OST ␣ .…”
Section: Enterocyte Metabolism Of Bile Acidsmentioning
confidence: 57%
“…Several in vivo studies were performed with SC-435 treatment in Hartley guinea pigs, miniature pigs, New Zealand White rabbits and dogs. Concordantly, these studies found an increase of faecal bile acid excretion, decreased total and LDL-cholesterol plasma levels, and enhanced expression of the hepatic LDL receptor, secondary to the upregulation of hepatic cholesterol 7α-hydroxylase (CYP7A1) expression (Huff et al 2002;West et al 2002West et al , 2003Bhat et al 2003;Telford et al 2003;Li et al 2004).…”
Section: Pharmacological Inhibition Of the Asbtmentioning
confidence: 70%
“…It is reasonable to speculate that a reduced ability to convert cholesterol to bile acids would lead to body cholesterol overload, with the subsequent development of atherosclerosis [Assmann et al 2006;Sudhop et al 2002;Rajaratnam et al 2000Rajaratnam et al , 1999Glucc et al1991]. Studies in animals have revealed that mice and rats [Guorong et al 2004;Bhat et al 2003;Post et al 2003;Lutton, 1990] do not develop experimental atherosclerosis, despite ingestion of a cholesterol-rich diet. They were able to react to the overload of cholesterol intake by excreting large amounts of bile acids.…”
Section: Introductionmentioning
confidence: 99%
“…statins), the development of atherosclerosis cannot be stopped in a significant number of patients. In addition to statins, low-density lipoprotein cholesterol (LDL-c) can be reduced by increasing the fecal bile acid waste and by compensatory hepatic upregulation of bile acid synthesis [Bhat et al 2003;Izzat et al 2000]. While a great deal of attention has been given to the factors that determine cholesterol homeostasis, cholesterol excretion via bile in patients with CAD has not been examined in depth.…”
Section: Introductionmentioning
confidence: 99%